Factors Related to the Event of Macrosomia in Infants at the Atikah Clinic for the Period of 2018-2020 - Nasution, Helmi Wardah (International Journal of Public Health Excellence (IJPHE), 2022)
Macrosomia or baby giant is a large newborn at the time of delivery of more than 4000 grams. Babies who are large for gestational age typically have swollen and red bodies. The emergence of these babies is due to several factors, the first factor is due to obese parents (heredity), the second is that pregnant women suffer from diabetes mellitus, the third factor is mothers who are overweight during pregnancy and the last factor is mothers who experience late pregnancy. time over post date. Based on the results of the initial survey, from the number of mothers giving birth as many as 76 cases, in the period 2018-2020 there were 15 cases (19.73%) experiencing macrosomia babies. The design of this research is analytic, namely the characterization technique directly through the explanation by the author and the approach, observation or data collection at the same time. Based on the results of the chi-square test, the value of p = 0.000 (p <0.05), which means that statistically it shows a significant relationship between the factor of gestational age and the occurrence of macrosomia in infants. Factors of multigravida pregnancy associated with the incidence of macrosomia in infants.